2013
DOI: 10.1103/physreve.88.062506
|View full text |Cite
|
Sign up to set email alerts
|

Biaxiality-induced magnetic field effects in bent-core nematics: Molecular-field and Landau theory

Abstract: Nematic liquid crystals composed of bent-core molecules exhibit unusual properties, including an enhanced Cotton-Mouton effect and an increasing isotropic (paranematic)-nematic phase transition temperature as a function of magnetic field. These systems are thought to be good candidate biaxial liquid crystals. Prompted by these experiments, we investigate theoretically the effect of molecular biaxiality on magnetic field-induced phenomena for nematic liquid crystals, using both molecular field and Landau theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Similarly, the critical field associated with a critical end point of the first-order transition line between the uniaxial and the paranematic phases, which has been observed for a fixed biaxiality parameter by various authors [6,11,12,15,31], corresponds to the value of the field, which makes our simple critical point reach the uniaxial limit ∆ = 0 for χ > 0; see the inset in Figure 2a. Again, the same qualitative behavior for the appearance of a critical end point in the uniaxial-paranematic transition was predicted for hard rods or hard plates with χ > 0 [32].…”
Section: Phase Diagrams In a Fieldsupporting
confidence: 71%
See 1 more Smart Citation
“…Similarly, the critical field associated with a critical end point of the first-order transition line between the uniaxial and the paranematic phases, which has been observed for a fixed biaxiality parameter by various authors [6,11,12,15,31], corresponds to the value of the field, which makes our simple critical point reach the uniaxial limit ∆ = 0 for χ > 0; see the inset in Figure 2a. Again, the same qualitative behavior for the appearance of a critical end point in the uniaxial-paranematic transition was predicted for hard rods or hard plates with χ > 0 [32].…”
Section: Phase Diagrams In a Fieldsupporting
confidence: 71%
“…In thermotropic systems, prompted by experimental results [11] for bent-core, intrinsically biaxial molecules with an essentially fixed shape, there have been studies on the combined effect of biaxiality and a magnetic field on the temperature of the first-order uniaxial to a paranematic phase transition, on the stability of the various phases, and on the presence of multicritical points [11][12][13][14][15][16]. In particular, within the phenomenological Landau-de Gennes theory, Mukherjee and Rahman [13] have identified the destabilization of the Landau point and its splitting into one critical and two tricritical points.…”
Section: Introductionmentioning
confidence: 99%
“…Only in 2004, Madsen et al [36] and Acharya et al [37] claimed the first observation of a thermotropic N b phase in a system of bent-core mesogens, i.e., a class of polar biaxial "banana"-shaped molecules with a C 2v symmetry. Various claims of observations of a thermotropic N b phase were later reported in systems of bent-core mesogens [38][39][40][41][42][43][44][45], promoting the idea that the C 2v symmetry plays a crucial role in the stabilization of N b phases.…”
mentioning
confidence: 99%
“…A detailed calculation of the effects of molecular biaxiality found that this may also lead to anomalously large field effects for the N-I transition. [14] In this work, we report on an unprecedented magnetic field-induced shifts of the isotropic-nematic phase transition temperature observed in liquid crystal dimers where two rigid linear mesogens are linked by flexible nonyl or heptyl chains. [15] The shapes of these molecules resemble nunchaku fighting sticks.…”
mentioning
confidence: 99%